Medical microbiology - Murray, Patrick R. (Elsevier/Saunders, 2013)
Newly reorganized to correspond with integrated curricula and changing study habits, this text is clearly written and easy to use, presenting clinically relevant information about microbes and their diseases in a succinct and engaging manner.